WANITA KARIR DALAM PANDANGAN ISLAM - ASRIATY ASRIATY (AL-MAIYYAH : Media Transformasi Gender dalam Paradigma Sosial Keagamaan, 2014)
Basically, women careers working outside and taking the responsibility to earn the money for the basic need in accordance with their skills and competencies show their independency. In other side, this becomes the causes increasing the negative effect of women career especially the way to arrange the time allocation as a wife in one side and as a mother in the other side. Being housewife should not be neglected to avoid the negative effect for the family. The women career phenomena still increases specially in the perspective of whether becoming women career specially for the wife will obstruct the husband right and children affection or not. This condition is considered to be avoided because can lead the broken home especially for the children mentality while their mothers are working outside.